Тиреопатії, індуковані аміодароном та інтерферонами - Бурдо, І. С.; Комісаренко, І. В. (Clinical Endocrinology and Endocrine Surgery, 2010)
In this article the clinical cases of thyroid pathologies which arouse after taking amiodaronum and interferons are described.